2019
DOI: 10.1128/jcm.00721-19
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Five Commercial Identification Platforms for Identification of Staphylococcus delphini

Abstract: The Staphylococcus intermedius group (SIG) is a collection of coagulase-positive staphylococci consisting of four distinct species, namely, Staphylococcus cornubiensis, Staphylococcus delphini, Staphylococcus intermedius, and Staphylococcus pseudintermedius. SIG members are animal pathogens and rare causes of human infection. Accurate identification of S. pseudintermedius has important implications for interpretation of antimicrobial susceptibility testing data and may be important for other members of the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…S. pseudintermedius is a rarely described pathogen in humans, though identification is increasingly common due to the use of more accurate diagnostic tools. 4 Similar to previous cases, our patient reported extensive physical contact with a dog, but unlike prior reports, she did not have predisposing medical conditions or suffer a traumatic bite. We hypothesize that her infection was due to either transient bacteremia from a distant colonized site or local spread from microtrauma to the foot, which the dog licked frequently, though she lacked evidence of overt spread directly from the skin.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…S. pseudintermedius is a rarely described pathogen in humans, though identification is increasingly common due to the use of more accurate diagnostic tools. 4 Similar to previous cases, our patient reported extensive physical contact with a dog, but unlike prior reports, she did not have predisposing medical conditions or suffer a traumatic bite. We hypothesize that her infection was due to either transient bacteremia from a distant colonized site or local spread from microtrauma to the foot, which the dog licked frequently, though she lacked evidence of overt spread directly from the skin.…”
Section: Discussionsupporting
confidence: 84%
“…6 Although MALDI-ToF MS is considered more accurate, incorrect species allocations also occur. 4 Methicillin-resistant and multidrug resistant strains of S. pseudintermedius have been described and are increasingly common. A recent case series 3 of S. pseudintermedius among 33 patients with chronic rhinosinusitis found an 82% resistance rate to penicillin and 27% to oxacillin.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis based on MALDI-TOF MS protein data was able to separate the S. pseudintermedius and S. delphini Antarctic isolates, place them together with corresponding type strains, and create separate clusters from S. intermedius and S. cornubiensis type strains. Unlike a recent report [72], mass spectrometry was unable to identify two Antarctic isolates of S. delphini using a MALDI-TOF MS-based scoring identification workflow.…”
Section: Discussionmentioning
confidence: 59%
“…The Vitek2 system database, which is used in our clinical laboratory, includes S. pseudintermedius. In contrast, other commercially available automated biochemical identification platforms such as the MicroScan WalkAway (Beckman Coulter, Inc., Brea, CA, USA) and BD Phoenix (BD Biosciences, Franklin Lakes, NJ, USA) database, do not include S. pseudintermedius (30). The true incidence of S. pseudintermedius as a cause of human infection may therefore be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed MALDI-TOF MS to be a rapid and accurate method for the species-level identification of SIG group members ( 30 , 33 , 34 ). However, the accurate species level identification of S. pseudintermedius depends on the database.…”
Section: Discussionmentioning
confidence: 99%